2007
DOI: 10.1353/cpr.0.0001
|View full text |Cite
|
Sign up to set email alerts
|

Using Information Technology to Improve Health Quality and Safety in Community Health Centers

Abstract: Problem-Community health centers (CHCs) face a unique set of challenges and can learn much from each other as they prepare for the adoption of health information technology (HIT).Purpose-This paper presents a research agenda aimed at providing information CHCs will need to successfully implement HIT.Key Points-Community health centers must be able to evaluate whether an investment in HIT is the best way to achieve improvements in health outcomes for their communities given the limited resources and high demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This study has several practical implications. Since previous studies found that training of the staff is critical in adopting a new system (Calman et al, 2007), and more specifically determines if fluoroscopy is used to position the patient (Dierckx et al, 2005), results of this study are remarkable. Approximately two thirds of the participants did not attend an external training.…”
Section: Strengths Limitations and Practical Implicationsmentioning
confidence: 75%
“…This study has several practical implications. Since previous studies found that training of the staff is critical in adopting a new system (Calman et al, 2007), and more specifically determines if fluoroscopy is used to position the patient (Dierckx et al, 2005), results of this study are remarkable. Approximately two thirds of the participants did not attend an external training.…”
Section: Strengths Limitations and Practical Implicationsmentioning
confidence: 75%
“…), websites, and additional resources pertinent to the patient's language needs. In studying HIT at community health centers in New York City, Calman, Kitson, and Hauser () noted that computerized support, such as electronic medical records and clinical decision support, can generate appropriate material from multilingual patient education databases. This streamlines the process for providers to supply their patients with language appropriate materials during the office visit.…”
Section: Solutionsmentioning
confidence: 99%
“…In fact, it has been suggested that information technology must play a central role in the redesign of the health care system, if substantial improvement in healthcare quality is to be achieved (1). There is also a growing interest in understanding the potential role of health IT in addressing healthcare disparities (2)(3)(4). In order to adequately and appropriately evaluate the potential of health IT to address healthcare disparities, health IT adoption and utilization barriers must be evaluated and understood.…”
Section: Human Factors Guidance To Prevent Healthcare Disparities Witmentioning
confidence: 99%
“…(1) subjects who are representative of the target population of EHR users, (2) representative tasks, and (3) measures of efficiency, effectiveness and subjective satisfaction.…”
Section: Designers and Developers Should Use The Common Industry Formmentioning
confidence: 99%